(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
Zinc oxide (ZnO), a compound that has been widely implemented in pig production due to its beneficial properties for the health and performance of pigs at an early age. In this research, the use of ZnO in pig feed was evaluated, focusing on the ability to prevent post-weaning diarrhea and its impact on the growth, immune response and intestinal health of pigs. For this, six treatments were compared at a dose of 3.250; 2.750; 2.150: 1.750; 1.450; 1.300 ppm and a control, for which 42 specimens from backyard farms were used, all uncastrated males, aged 24 d, belonging to the Landrace x Criollo breed, whose initial weight has an average of 5,8 ± 0,4 kg, grouped into 2 animals per treatments. The results show that a dose of 2.750 ppm of Zn oxide improves the intestinal health of animals by reducing the prevalence of post-weaning diarrhea, providing long-term positive effects, observing an improvement in the absorption of nutrients, which manifests in an increase in performance and productive capacity by obtaining a greater weight gain, even with a dose of 1.450 ppm, which allows a synergistic effect by achieving the health improvement of the piglets and obtaining a greater weight gain, which indicates that this treatment It is the best option from the point of view of benefits and costs for the producer.